UPAYA MEWUJUDKAN PENDIDIKAN BERKEADILAN GENDER PERSPEKTIF ISLAM - hasim, sarifa suhra (An - Nisa`, 2011)
One of the fulfillment form of the rights and obligations of every individual is education. In Islam, the rationality and spiritual fulfillment can be done by learning to obtain a broad of knowledge as a way to understand the religion and solutions in building the world. Islam as a religion calls for all believers to seek knowledge whatever, as long as not contrary to the mission af humanity and as a servant of , God and the caliph on earth without exception. This means that Islam gives recognition of the rights to all people including womens education are limitless from basic education to higher education, according to each individuals interests. This paper tries to rip off that is essentially the spirit of Islamic education is the "freedom and democracy" are not looking at gender.Therefore, Islamic education is a process of transfer of knowledge from educators to the learners towards the achivement of perfect man of harmony, balance without distinguishing between men and women, this paper further explains that achieves the gender equitable education on Islamic perspective, it would require educators and learners who understands the values of equatity and gender justice.